The Warning with the Phrase "Beware of you" In Imam al-Nasa'i's Sunan al-Sughra "al-Mujtaba": A Collection and Study - Firas Hamid Shaker El-Tayyif, (Islamic Sciences Journal, 2025)
ABSTRACT Praise be to Allah, Lord of the Worlds, and prayers and peace be upon the trustworthy Prophet, sent as a mercy to the worlds, and upon his family and companions, all of them, and those who follow his guidance until the Day of Judgment. This research came under the title: “The warning with the phrase ‘Beware of you’ according to Imam al-Nasa’i - may Allah have mercy on him - in al-Sunan al-Sughra ‘al-Mujtaba’ - Collection and Study” to address the hadiths in which the prophetic warning with the phrase mentioned in al-Sunan al-Sughra was mentioned. The research consists of an introduction, two chapters, and a conclusion. The first chapter deals with a brief study of the life of Imam al-Nasa’i - may Allah have mercy on him - while the second chapter studies the three hadiths in which the warning is mentioned with the wording: “Beware” and which are included in the Sunan al-Sughra. Then after that, there is a conclusion in which I mention the most important results I have reached in this research.